2015
DOI: 10.1016/j.bbalip.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ activation induces hepatic long-chain acyl-CoA synthetase 4 expression in vivo and in vitro

Abstract: The arachidonic acid preferred long-chain acyl-CoA synthetase 4 (ACSL4) is a key enzyme for fatty acid metabolism in various metabolic tissues. In this study, we utilized hamsters fed a normal chow diet, a high-fat diet or a high cholesterol and high fat diet (HCHFD) as animal models to explore novel transcriptional regulatory mechanisms for ACSL4 expression under hyperlipidemic conditions. Through cloning hamster ACSL4 homolog and tissue profiling ACSL4 mRNA and protein expressions we observed a selective upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…Depletion of PPAR␦ significantly lowered LPCAT3 mRNA levels to ϳ64% of control (p Ͻ 0.001) and also reduced levels of ACSL4 and ACSL3 mRNA, both of which are known target genes of PPAR␦. In contrast, expression of PPAR␦ shRNA in HepG2 cells did not diminish ACSL1 mRNA levels, which was consistent with our previous in vivo observations that PPAR␦ activation increased ACSL4 and ACSL3 expressions without affecting ACSL1 mRNA levels in hamster liver (18,27).…”
Section: Hepatic Depletion Of Ppar␦ Leads To the Suppression Of Lpcatsupporting
confidence: 92%
See 4 more Smart Citations
“…Depletion of PPAR␦ significantly lowered LPCAT3 mRNA levels to ϳ64% of control (p Ͻ 0.001) and also reduced levels of ACSL4 and ACSL3 mRNA, both of which are known target genes of PPAR␦. In contrast, expression of PPAR␦ shRNA in HepG2 cells did not diminish ACSL1 mRNA levels, which was consistent with our previous in vivo observations that PPAR␦ activation increased ACSL4 and ACSL3 expressions without affecting ACSL1 mRNA levels in hamster liver (18,27).…”
Section: Hepatic Depletion Of Ppar␦ Leads To the Suppression Of Lpcatsupporting
confidence: 92%
“…PPAR␦ activation in liver is known to activate a transcriptional program to increase cellular abundances of multiple enzymes to modulate FA and PL metabolism (31). Our previous studies have identified ACSL4 as a new molecular target of PPAR␦ in liver cells (18). In this study, we explored the possibility that activation of PPAR␦ in liver tissue might not only increase ACSL4 cellular abundance and its enzymatic activity but could also affect the metabolic fates of ACSL4-produced PUFA-CoAs by altering the availability of ACSL4 fatty substrates, its interacting proteins, and downstream effectors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations